2004
DOI: 10.1177/147592170400300401
|View full text |Cite
|
Sign up to set email alerts
|

Damage Quantification of Flexurally Loaded RC Slab Using Frequency Response Data

Abstract: A one-way reinforced concrete (RC) slab was subjected to short-duration concentrated impact load and its dynamic characteristic for the virgin and damaged conditions were studied using two signal processing techniques. The recorded strain and acceleration signals were analyzed using the Fast Fourier Transform (FFT) and the Hilbert Huang Transform (HHT). From these analyses, the percentage reductions in the modal frequency for varying degrees of damage (or magnitude of applied load) were obtained. Based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…5. Similarly to the previously reported findings [11,15], the frequency reduction is proportionally larger for the starting load increments. Only near and after the yielding level is reached, the rate of reduction is slowed down.…”
Section: Modal Analysis Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…5. Similarly to the previously reported findings [11,15], the frequency reduction is proportionally larger for the starting load increments. Only near and after the yielding level is reached, the rate of reduction is slowed down.…”
Section: Modal Analysis Resultssupporting
confidence: 72%
“…It was observed from the experimental modal analysis of the incrementally damaged RC beams and slabs [8,[11][12][13] that their frequency of the 1st vibration mode can be reduced up to 30% This paper has been published under the following reference: Pešić, N., Živanović, S., Dennis, J. when the yielding of the tensile reinforcement occurs [14,15]. Such magnitude of frequency reduction, being a consequence of structural damage, gave rise to the concept of damage identification by means of modal testing [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Razak et al [ 27 ] studied the modal parameters of RC beams under the influence of steel corrosion and concluded that damping is an unreliable corrosion damage parameter of RC beams, while the natural frequency can effectively reflect the structural capacity changes caused by the steel corrosion in the test beams. Koh et al [ 28 ] and Capozucca et al [ 29 ] illustrated that the damage of the RC structure caused by steel corrosion will inevitably lead to the change of performance such as modal frequency, stiffness, damping ratio, and so on. However, these researches did not analyze the sensitivity of natural frequency response to the steel corrosion, and it is unknown whether the occurrence of steel corrosion can be identified even if no cracks can be observed on the surface of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…10 The wafi of the IMFs for EEG signal without spike wave, and spike I, II, and III sample waves Fig. 11 The wami of the IMFs for EEG signal without spike wave, and spike I, II, and III sample waves Spike I, II, and III waves of theγbands in the interval of 0-0.096 s were higher than that of the energy of RF to its referred total energy for the EEG signal without spike waves of theγband in the interval of 0-0.096 s. The frequency with the most power was determined using the weighted average frequency of the iIMF waf i , and the weighted average magnitude of the iIMF wam i [31][32][33] (http://www.vis.caltech.edu/%7Erodri/Wave_clus/Wave_ clus_home.htm). The weighted average frequency of the ith IMF is defined as follows:…”
Section: Discussionmentioning
confidence: 99%